IMPLEMENTATION OF THE RICE-POOR DIRECT CASH ASSISTANCE (BLT) PROGRAM IN OVERCOMING POVERTY DUE TO COVID-19 IN BANYU TAJUNG VILLAGE, TANJUNG DISTRICT, TABALONG REGENCY - Saprudin; Ahmat Harahap (p3m.stiatabalong.ac.id, 2022)
Research on the Implementation of the Rice for the Poor (Raskin) Direct Cash Assistance (BLT) Program in Overcoming Poverty Due to Covid 19 in Banyu Tajun Village, Tanjung sub-district, Tabalong Regency, is important to do, because there are still problems related to the Rice for the Poor Direct Cash Assistance (BLT) program (Raskin). ) In Overcoming Poverty Due to Covid 19 in Banyu Tajun Village, Tanjung sub-district, Tabalong Regency. The purpose of this study was to find out and analyze the Implementation of the Rice for the Poor (Raskin) Direct Cash Assistance Program in Overcoming Poverty Due to Covid 19 in Banyu Tajun Village, Tanjung sub-district, Tabalong Regency. Types and approaches to research using descriptive qualitative research. Data collection techniques carried out include the collection of observational data, interviews and documentation. The informants used in this study amounted to 5 people. After the data is collected, it is then analyzed using techniques including data reduction, presentation of data, and verification or drawing conclusions. The data is then tested for data credibility to assess the truth of the qualitative research findings. Based on the results of the discussion above, it shows that regarding the Implementation of the Direct Cash Assistance Program (BLT), seen from the communication aspect, the transmission indicator is categorized as sufficiently implemented, from the clarity indicator it is categorized as sufficiently implemented, and from the consistency indicator it is categorized as sufficiently implemented. From these results it can be concluded that the Implementation of the Direct Cash Assistance Program (BLT) seen from the communication aspect in Banyu Tajun Village, Tanjung sub-district, Tabalong Regency is categorized as implemented Keywords: Implementation, Program, Direct Cash Assistance (BLT)